Understanding membrane fouling of oil in water emulsion-based separations - Tanudjaja, Henry Jonathan (2019)
Oil in water emulsion could be present in many industries, in terms of product or waste and the separation of the oil emulsion from the water is always a challenge due to its small size which could not efficiently handle by conventional separation technologies. Membrane technology has been increasingly employed for this separation process due to its selective and efficient performance, but still has a drawback which is the fouling. Studies regarding the membrane fouling due to oil in water emulsions are done by Direct Observation through Membrane (DOTM) in the microfiltration system to explore more understanding about the fouling. It is observed that different operation parameter could play a role in the membrane fouling. Higher crossflow velocity and lower oil feed concentration decrease the fouling propensity regardless the type of oil used, meanwhile higher viscosity slows down oil emulsion movement on the membrane surface, and bidispersity of the oil emulsion also affects the fouling mechanism. Shear-induced diffusion model helps to predict the critical flux of the oil emulsion separation. From the DOTM images, it is understood that oil emulsion fouling evolves from individual deposit into moving stripes or became a moving oil cake layer, which is a different characteristic in comparison to the unmoved latex particle cake layer. Interaction energy model reveals the physical understanding of the interaction between oil emulsion with the membrane surface during the fouling phenomenon.